The influence of breast milk microbiota from HIV-infected women on infant gut microbiota colonization within the first two weeks of life - Munjoma, Privilege Tendai; Wyss, Jacqueline; Mazhandu, Arthur John; Jordi, Sebastian Bruno Ulrich; Ganal-Vonarburg, Stephanie Christine; Zinyama-Gutsire, Rutendo; Katsidzira, Leolin; Yilmaz, Bahtiyar; Misselwitz, Benjamin; Duri, Kerina (Frontiers in Microbiomes, 2026)
BackgroundThe human milk microbiota significantly contributes to the shaping of the infant gut microbiota during early life. Influenced by maternal factors such as birth mode, diet, and breastfeeding practices, these microbial communities are critical for infant health. We explored the effect of maternal human immunodeficiency virus (HIV) status and breastfeeding practices on breast milk microbiota composition and its correlation with infant gut microbiota between 7 and 14 days postpartum.MethodsBreast milk and stool microbiota from 68 lactating HIV-infected and uninfected women and their 69 infants (including one set of twins) were characterized using 16S rRNA gene sequencing. Sociodemographic and clinical data were also collected.ResultsBreast milk microbiota was dominated by Streptococcus and Gemella, whereas the infant gut microbiota showed a co-occurrence of early colonizers such as Enterobacteriaceae_unclassified, Bifidobacterium, and Streptococcus. In contrast, maternal stool exhibited greater microbial diversity, enriched in Romboutsia and Clostridium_sensu_stricto_1. Small, non-significant differences were observed in alpha diversity by maternal HIV status (Cohen’s d ≈ −0.38; 95% CI: −3.88 to 0.07), suggesting possible modest to no effects, even though p-values were not significant. Clostridium_sensu_stricto_1 was more abundant in HIV-uninfected mothers. Infant HIV exposure and maternal antibiotic prophylaxis had no detectable effect on gut microbiota diversity or composition. Notably, positive correlations were observed between breast milk and infant gut taxa abundances, including Gemella (ρ = 0.33, p = 0.010) and Enterobacteriaceae_unclassified (ρ = 0.31, p = 0.016). SourceTracker analysis indicated that 31.5% of infant gut taxa were traceable to breast milk, with higher contributions in HIV-exposed infants (41%) compared with HIV-unexposed infants (25.6%).ConclusionThis study is among the first to investigate breast milk microbiota in the context of HIV infection in Zimbabwe. We demonstrated that maternal HIV infection and cotrimoxazole prophylaxis did not measurably alter breast milk or early infant gut microbiota composition. Despite limited statistical power to detect small-to-moderate effects, taxa-level correlations and microbial source tracking supported breast milk as a major contributor to early gut colonization. These results underscore breast milk–mediated microbial seeding in early life, while highlighting the need for larger longitudinal studies to define how maternal HIV status may subtly influence vertical microbial transfer.